Pengaruh Senam Hamil terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil TM III di Puskesmas Birem Bayuen Aceh Timur Tahun 2024 - Wilda Wilda; Ester Simanullang (Inovasi Kesehatan Global, 2025)
Back pain is a disorder that is often encountered in pregnant women, this is caused by the shift of gravity towards the body's core towards the front. The aim of the research was to determine the relationship between pregnancy exercise and complaints of low back pain in pregnant women III at the Birem Bayuen Community Health Center. This research uses an experimental research design. The sample for this study was all pregnant women in the third trimester at the Birem Bayuem Community Health Center who were included. The results of this study were lower back discomfort in pregnant women before pregnancy activities, more than half of respondents reported low back pain on a scale of 3 (very painful). Most respondents reported reduced back pain, as many as 7 respondents reported no pain. This is lower back pain in pregnant women III after pregnancy exercise. Through this research, pregnant women understand the benefits of pregnancy exercise during pregnancy, especially during the third trimester of pregnancy, which has a very good impact so that mothers feel comfort and reduce complaints during pregnancy, such as lower back pain in particular